Predictability of crowding resolution in clear aligner treatment - Adriana Fiori; Giuseppe Minervini; Ludovica Nucci; Fabrizia d'Apuzzo; Letizia Perillo; Vincenzo Grassia (SpringerOpen, 2022)
Abstract Background To assess the predictability of crowding resolution and the efficacy of different strategies to gain space during clear aligners treatment. Methods A total of 10 clinicians were randomly recruited using the Doctor Locator by Align Technology (California). For each clinician, four consecutive patients treated with aligners and manual stripping were selected for a total of 40 subjects. Thus, 80 arches were collected and uploaded on the Orthoanalyzer software for arch measurements. The data were gained on the starting arch form (T0), on the virtual arch developed with digital planning (vT1), and on the arch form achieved at the end of the aligner sequences (T1). The following parameters were scored: Little's Irregularity Index, transversal arch diameters, (intercuspid, interpremolar, and intermolar width), incisor position/arch length, and enamel interproximal reduction (IPR). Results For all the measurements, statistically significant differences were found at different stages. The predictability of crowding resolution was very high, ranging from 87% in the upper arch and 81% in the lower one. Among the different strategies to gain space, variations in sagittal incisor position were predictable, with a value of 70% both in the upper and lower arch. Conversely, changes in arch diameters were less reliable varying between 49 and 67% in the lower arch and 59-83% in the upper one. Moreover, IPR was the least accurate procedure, wavering at 49% in the upper arch and 42% in the lower arch. Conclusions The predictability of crowding resolution during treatment with aligners was high. However, the virtual arch forms obtained at the end of digital planning (vT1) did not correspond with the arch forms at the end of the aligner sequences (T1). The IPR was the least predictable strategy to gain space, being, perhaps, an operator-dependent procedure.